2020
DOI: 10.3168/jds.2019-17494
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of starter-induced ruminal acidosis in calves before, during, and after weaning

Abstract: The objectives were to nutritionally induce or blunt ruminal acidosis in young calves and to compare indicators of rumen and systemic health. Ten bull calves (n = 5/diet) were ruminally cannulated at 3 wk of age and received milk replacer and 1 of 2 calf starter diets that were designed to cause (AC; pelleted, 42.7% starch, 15.1% neutral detergent fiber, 57.8% nonfiber carbohydrates) or blunt (BL; texturized, 35.3% starch, 25.3% neutral detergent fiber, 48.1% nonfiber carbohydrates) ruminal acidosis. Mean birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 34 publications
4
32
1
Order By: Relevance
“…However, studies also reported that high-grain diets caused corneum thickness to remain similar to that found with high-forage diets, but corneum layer sloughing increased (Steele et al, 2011. Ruminal lesions were reported in 2 groups of calves fed either a 42.7 or 35.3% starch diet at 17 wk of age; however, lesions were less severe in calves fed the lower starch diet (Gelsinger et al, 2020). The number of cells increased numerically in the current study over time, which may have resulted in an increase in corneum thickness.…”
Section: Discussionmentioning
confidence: 81%
“…However, studies also reported that high-grain diets caused corneum thickness to remain similar to that found with high-forage diets, but corneum layer sloughing increased (Steele et al, 2011. Ruminal lesions were reported in 2 groups of calves fed either a 42.7 or 35.3% starch diet at 17 wk of age; however, lesions were less severe in calves fed the lower starch diet (Gelsinger et al, 2020). The number of cells increased numerically in the current study over time, which may have resulted in an increase in corneum thickness.…”
Section: Discussionmentioning
confidence: 81%
“…This work was conducted by using our established acidosis-inducing/blunting model in young calves [ 26 ]. Per our previous report, rumen pH was reported in our recently published work [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Calves included in this study were part of a larger study that was published [ 26 , 27 , 28 ]. Throughout the experiment, all animal protocols (A005848) were approved by the Animal Care and Use Committee at the University of Wisconsin–Madison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, increased rumen motility and digesta passage out of the rumen, in combination with increased time spent ruminating, prevents excessive ruminal pH drop, via increased volatile fatty acid (VFA) passage to the omasum and increased delivery of buffers to the rumen within saliva. A very low pH is commonly reported in calves fed grain based starter feeds ad libitum and there are indications that it may have a negative impact on performance of calves [29]. Beneficial impacts of forage intake on rumen development are further supported by higher expression of some VFA transporters in ruminal epithelium of calves offered forages in addition to grain based starter feed, compared to those fed only concentrates [7], indicating that the development of ruminal epithelium may also be, to some extent, positively affected by forage intake.…”
Section: Why Is Forage Important For Young Calves?mentioning
confidence: 99%